Aiding empirical research on the commercial determinants of health: a scoping review of datasets and methods about lobbying - Jennifer Lacy-Nichols; Madalyn Quinn; Katherine Cullerton (BMC, 2023)
Abstract Background To support public health researchers and advocates seeking to challenge the influence of powerful commercial actors on health, it is necessary to develop a deeper understanding of corporate political activities. This project explores political science scholarship analysing lobbying to identify new datasets and research methods that can be applied to public health and stimulate further research and advocacy. Methods We undertook a systematic scoping review of peer-reviewed and grey literature reports analysing the practice of lobbying. Titles and abstracts of 4533 peer-reviewed and 285 grey literature reports were screened, with 233 peer-reviewed and 280 grey literature reports assessed for eligibility. We used a two-stage process for data extraction. In stage 1, we collected two pieces of information from all included studies: data sources and indicators used to measure lobbying. For the second stage, data extraction was limited to 15 studies that focused on meetings. Results The most common indicators used to measure lobbying activity were: registrations of active lobbyists; expenditure on lobbying; meetings; written comments and submissions made to government consultations; bills; and committee participation. A range of different data sources were used to analyse lobbying, including from governments, not-for-profits and commercial sources. All 15 studies analysing lobbyist meetings were from high-income contexts. The studies analysed three key variables: the types of government actors targeted by lobbying; the policies of interest; and the lobbyists and/or their clients. The studies used a range of taxonomies to classify policy issues and the types of actors engaged in lobbying. All studies discussed challenges with accessing and analysing lobbying data. Conclusions There is enormous potential for public health research and advocacy concerned with commercial lobbying to learn from political science scholarship. This includes both conceptual frameworks and sources of empirical data. Moreover, the absence of good quality transparency internationally emphasises the importance of advocacy to support policy change to improve the quality of political transparency to make it easier to monitor commercial lobbying.